The role of Caveolin-1 in tumor-derived extracellular vesicle biology and its implications - Kailasam Mani, Satish; Lamaze, Christophe; Saquel, Cristian (Frontiers in Cell and Developmental Biology, 2025)
Tumor-derived extracellular vesicles (TEVs) are increasingly recognized as key mediators of intercellular communication between cancer cells and their environment, a process crucial for tumor progression. TEVs can act locally on neighboring cells or travel long distances to impact remote tissues, thereby promoting tumor growth, cell invasion, pre-metastatic niche formation, and ultimately, metastasis. Despite significant insights into the molecular mechanisms by which TEVs shape the tumor microenvironment (TME) and induce pro-metastatic effects in recipient cells, many questions remain unanswered. Recent studies suggest that caveolae, invaginations of the plasma membrane with critical roles in cellular mechanics, may play an important role in TEV-mediated metastatic trait acquisition by cancer cells. The presence of caveolin-1 (Cav1) in EVs supports its involvement in EV dynamics, including biogenesis, secretion and uptake by recipient cells. Further research into the role of Cav1 in EV-mediated cancer progression could pave the way for improved diagnostic tools and novel therapeutic strategies in cancer treatment.